2018
DOI: 10.4995/wrs.2018.5217
|View full text |Cite
|
Sign up to set email alerts
|

Nutritive value of sun-dried common reed (Phragmites australis) leaves and its effect on performance and carcass characteristics of the growing rabbit

Abstract: The nutritive value and potential use of sun-dried common reed (<em>Phragmites australis</em>) leaves (CRL), for growing rabbits was studied by comparing 3 diets (regression method) containing an increasing incorporation rate of CRL: 0% (control, CRL0), 15% (CRL15) and 30% (CRL30) in substitution for the control diet (356 g neutral detergent fibre (NDF) and 197 g crude protein (CP)/kg). Three groups of 37 rabbits (individually caged) were fed the 3 diets <em>ad libitum</em> from weaning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 41 publications
2
6
0
2
Order By: Relevance
“…Average daily feed intake was unaffected by the genotype, and it was similar to that reported by several authors on different local populations and strains [15,28]. Our local population showed a similar average daily gain than other local populations [24,29]. However, the average daily gain was 19% higher in the synthetic line, but it was still lower than gains of different reported in other lines such as Hyla line (−16%) [30], New Zealand rabbits (−6%) [31], and V line (−11%) [28].…”
Section: Discussionsupporting
confidence: 90%
“…Average daily feed intake was unaffected by the genotype, and it was similar to that reported by several authors on different local populations and strains [15,28]. Our local population showed a similar average daily gain than other local populations [24,29]. However, the average daily gain was 19% higher in the synthetic line, but it was still lower than gains of different reported in other lines such as Hyla line (−16%) [30], New Zealand rabbits (−6%) [31], and V line (−11%) [28].…”
Section: Discussionsupporting
confidence: 90%
“…Most of the research conducted on rabbits in Algeria to date has often focused on carcass production, fertility and yield (Zerrouki et al, 2014;Belabbas et al, 2016;Kadi et al, 2018;Belabbas, 2019). To the best of our knowledge, in Algeria, studies about rabbit meat production are scarcely reported.…”
Section: W O R L D R a B B I T S C I E N C Ementioning
confidence: 99%
“…atteindre les valeurs recommandées pour les lapins en engraissement. En plus du fait que l'estimation de l'ED à partir des tables est inexacte [4], cette situation serait liée, notamment dans l'aliment expérimental, aux apports nuls en énergie des feuilles de roseau comme rapporté par Kadi et al [2]. Les apports protéiques des deux aliments dépassent largement les prévisions ainsi que les recommandations pour les lapins en croissance [3] et qui sont de 15%.…”
Section: Les Aliments Expérimentauxunclassified
“…De même, les feuilles de Roseau (Phragmites australis), disponibles en grande quantité et non valorisées, sont une bonne source de fibres pour le lapin en engraissement. Selon Kadi et al [2], elles contiennent au stade de maturité (en % de MS) 69% NDF, 41% ADF et 11,5% d'ADL alors que leur apports en ED et PD sont très faibles : apports nuls en ED et 32 g/kg MS de protéines digestibles.…”
Section: Introductionunclassified